Clinicopathological features of hepatocellular carcinoma with fatty change: Tumors with macrovesicular steatosis have better prognosis and aberrant expression patterns of perilipin and adipophilin. Issue 4 (12th January 2020) - Kubota, Naoto; Ojima, Hidenori; Hatano, Mami; Yamazaki, Ken; Masugi, Yohei; Tsujikawa, Hanako; Fujii‐Nishimura, Yoko; Ueno, Akihisa; Kurebayashi, Yutaka; Shinoda, Masahiro; Kitago, Minoru; Abe, Yuta; et al.
Abstract : The clinicopathological characteristics of steatosis in hepatocellular carcinoma (HCC) remain unclear. Here, we elucidate the features of macrovesicular steatosis (MaS) and microvesicular steatosis (MiS) in HCC and their relationships with background liver steatosis. A total of 165 HCC lesions were classified as MaS‐HCC, MiS‐HCC, or conventional HCC (cHCC) according to the cutoff value of 30% MaS or MiS in tumor cells. We analyzed the clinicopathological differences among these groups. MaS‐HCC had less portal vein invasion, a higher proportion of HCC with intratumoral fibrosis, and a lower cumulative risk of recurrence than MiS‐HCC or cHCC. Moreover, both MaS‐HCC and MiS‐HCC had lower incidences of hepatitis virus infection and higher levels of HbA1c than cHCC. Background liver steatosis was also higher in MaS‐HCC than in cHCC. Immunohistochemical expression of perilipin (Plin1) and adipophilin (ADRP), major proteins expressed on lipid droplet membranes, revealed that almost all lipid droplets in HCC were Plin1 negative, whereas those in background liver were positive. In contrast, ADRP was expressed on lipid droplets in both HCC and background liver. We concluded that MaS‐HCC and MiS‐HCC were associated with metabolic abnormalities but exhibited different biologic behaviors. Furthermore, lipid droplets in HCC were pathophysiologically different from those in background liver.